2009
DOI: 10.1074/jbc.m808029200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into the Activation Mechanism of Human Pancreatic Prophospholipase A2

Abstract: Pancreatic phospholipase A2 (phospholipase A2 group 1B, G1B) belongs to the superfamily of secreted phospholipase A2 (PLA2) enzymes. G1B has been proposed to be a potential target for diseases such as hypertension, obesity, and diabetes. Human pancreatic prophospholipase A2 (pro-hG1B) is activated by cleavage of the first seven-residue propeptide (phospholipase A2 propeptide, PROP). However, questions still remain on the mode of action for pro-hG1B. In this work, we expressed prohG1B in Pichia pastoris and det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…The authors suggested that human GIB sPLA 2 may use a different activation mechanism in which GIB sPLA 2 switches from monomeric to trimeric form when it associates with the membrane using the highly positive charged trimer back side. 40 The crystal structure of the trimeric form has also been shown in studies on cobra venom 41 and Naja naja GIA sPLA 2 s. 42 Anion-assisted dimer crystal structures were reported for other pancreatic sPLA 2 s. 43 While the existence of dimeric and trimeric forms may be a functionally important feature of these sPLA 2 s, the higher oligomeric states of sPLA 2 structures are found under high concentration crystallization conditions, so they may not be representative of the real physiological state. Whether the trimeric or dimmeric form is important for sPLA 2 catalysis or not requires further investigation.…”
Section: Secreted Phospholipase A2 (Spla2 Groups I Ii Iii V Ixmentioning
confidence: 99%
“…The authors suggested that human GIB sPLA 2 may use a different activation mechanism in which GIB sPLA 2 switches from monomeric to trimeric form when it associates with the membrane using the highly positive charged trimer back side. 40 The crystal structure of the trimeric form has also been shown in studies on cobra venom 41 and Naja naja GIA sPLA 2 s. 42 Anion-assisted dimer crystal structures were reported for other pancreatic sPLA 2 s. 43 While the existence of dimeric and trimeric forms may be a functionally important feature of these sPLA 2 s, the higher oligomeric states of sPLA 2 structures are found under high concentration crystallization conditions, so they may not be representative of the real physiological state. Whether the trimeric or dimmeric form is important for sPLA 2 catalysis or not requires further investigation.…”
Section: Secreted Phospholipase A2 (Spla2 Groups I Ii Iii V Ixmentioning
confidence: 99%
“…We carried out multitemplate modeling based on the crystal structures of hGX sPLA 2 (Protein Data Bank code 1LE7 (residue nos. 43-165) (32)), PropGIB (Protein Data Bank code 1HN4 (9)), and ProhGIB sPLA 2 (Protein Data Bank code 3ELO, (33)). The overall structure and the side chain positions are conserved in the model when compared with the experimental structure of hGX.…”
Section: Methodsmentioning
confidence: 99%
“…These enzymes are classified into different groups based on their primary sequence structures and the positions of their disulfide bonds [1]. While the structures of group I and group II PLA 2 s have been well characterized from different sources including humans [2][3][4][5], there exists only one representative crystal structure known so far in the group III which is that of the bee venom PLA 2 [6]. The structure of this group III PLA 2 is completely different from those of group I Abbreviations: PLA2, phospholipase A2; ExPASy, Expert Protein Analysis System; DS, Discovery Studio; ABNR, adopted basis set Newton-Raphson; CHARMM, Chemistry at HARvard Molecular Mechanics; PROCHECK, protein structure check; r.m.s.d., root mean square deviation; ps, pico seconds.…”
Section: Introductionmentioning
confidence: 99%